THE IMPLEMENTATION OF STUDENTS ACTION LEARNING STRATEGY TO IMPROVE STUDENTS’ SPEAKING SKILL - Jusmaniar N; Sulviana Sulviana; Aulia Rinjany Putri Sulya (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2023)
This study intends to increase students' English speaking skills through the use of learning methodologies. This study was designed for quantitative approaches and included a time series design. This investigation was carried out in class VIII, with forty students participating. This study uses clusters to collect data samples, and the instrument utilized is a speaking exam. During each of the four meetings, data was collected using a pre-test and post-test format. To determine the findings of the problem formulation, researchers employed SPPS 24. According to the research findings, the average value of pre-test 1 is 59.13, followed by pre-test 2 at 62.0, pre-test 3 at 58.25, and pre-test 4 at 58.38. The average values for post-test 1 are 70.38, post-test 2 is 72.75, post-test 3 is 76.75, and post-test 4 is 74.9. According to the pre-test and post-test results, students experienced changes in the learning process, and there was a slight increase in speaking comprehension in English, so it can be concluded that, while the pre-test score decreased, the post-test results test had an average score that slightly increased from before after researchers used action learning strategies.